El Terciario de la Puna en tiempos de la ingresión marina paranense - Alonso, Ricardo Narciso (2000)
I report here the situation of the Puna region during the Miocene marine ingression known as paranense. Also, I make an update of the discussion related with the timing and distribution of the Parana and Pebasian seas in the Andean foreland. The Tertiary pos-Incaic rocks of the Puna region are related with main cycles: red-beds (Eocene s.l.), formed during a foreland stage previous to the marine ingression and clastic and evaporites deposits with interlayered tuffs (Neogene). These deposits are widely distributed and lie in angular unconformity on Paleozoic rocks (Ordovician). The Eocene red beds were deposited in an exorreic environment, with Atlantic drainage, in a benign climate, and contain a fauna of primitive mammals associated with turtles and crocodiles. The Neogene rocks, synchronic with the Miocene marine ingression, were deposited in a tectonic setting of intra-arc/intra-plateau, in an arid climate and have important concentrations of evaporites (halite, gypsum and borate). The Puna Tertiary rocks contain the most important borate deposits of South America deposited during the Late Miocene (6±1 Ma). The region was in elevation at the time that the paranense marine ingression covered widely the interior of the Argentine Republic. Pebasian and Parana seas reflect tectonic-loading subsidence of the Andean foreland related to important Miocene shortening. The coincidence of this shortening with the 12 Ma high stand of sea level controlled the marine flooding of most of the South America foreland basins. The Quechua tectonic front during the Miocene was an effective barrier to isolate the Puna during the marine ingression.